Does dulaglutide impact a composite outcome reflecting atherosclerosis? A post-hoc analysis of the REWIND trial. (3rd October 2022) - Ferrannini, G; Mellbin, L; Kirabo, F; Ramasundarahettige, C; Herstein, H G; Ryden, L
Abstract: Background: It has been postulated that the cardioprotective effect of glucagon-like peptide-1 receptor agonists (GLP-1 RA) in patients with type 2 diabetes (T2DM) may retard the progression of atherosclerosis. Purpose: The aim of this post-hoc analysis of the REWIND trial was to test the hypothesis that treatment with dulaglutide impacts a clinical outcome that reflects atherosclerosis in patients with type 2 diabetes (T2DM). Methods: In the double-blind, placebo-controlled REWIND trial recruiting 9901 patients (46.3% women, mean age 66 years) with T2DM and cardiovascular disease (CVD) or varying levels of CV risk, a weekly subcutaneous injection of dulaglutide 1.5 mg reduced the hazard of MACE by 12% versus placebo. This post hoc analysis assessed the impact of dulaglutide on atherosclerosis-related outcomes comprising a composite of the first of CV death, nonfatal myocardial infarction, nonfatal ischaemic stroke and any revascularization including coronary, peripheral or carotid. Cox proportional hazards models were used to estimate the effect of randomized treatment. The effect in selected subgroups (Table 1) was estimated by including each subgroup and an interaction term in the model for the primary outcome. The composite of any component of the primary endpoint and non-cardiovascular death was considered as a secondary outcome. Results: The primary endpoint occurred in 799 (16.1%) patients in the dulaglutide group and 870 (17.6%) patients in the placebo group (incidence rates: 3.25/100 person-years vs 3.58/100 person-years; HR 0.91, 95% CI 0.83–1.00; p=0.05) during a median follow-up of 5.4 years. This finding was consistent regardless of sex, body mass index, previous CVD or not and diabetes duration. The incidence of the secondary outcome was also lower in the dulaglutide group (HR; 95% CI: 0.91; 0.83–0.99; p=0.03). Conclusion: Dulaglutide was associated with a 9% reduced index of atherosclerosis in patients with T2DM and CVD or high CV risk. This finding supports the hypothesis that dulaglutide may retard progression of atherosclerosis. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): EliLilly and Company